Feasibility of carbon dioxide absorption by NaOH solution in a rotating packed bed with blade packings. (November 2015) - Lin, Chia-Chang; Chu, Ching-Rong
Highlights: CO2 absorption was performed in RPB with blade packings by NaOH solution. The removal efficiency of CO2 increased with rotational speed, liquid flow rate, and NaOH concentration. The removal efficiency of CO2 decreased with gas flow rate and CO2 concentration. RPB with blade packings is an effective contactor for CO2 absorption. Abstract: The rotating packed bed (RPB) with blade packings was applied to absorb carbon dioxide (CO2 ) from gas streams by NaOH solution. The RPB with blade packings had an inner radius of 1.6 cm, an outer radius of 10.8 cm, and an axial height of 3.0 cm. Rotational speeds ranged from 600 to 1800 rpm, providing 25–225 equiv. gravitational force. The removal efficiency of CO2 was determined at various values of operating parameters, including the rotational speed, gas flow rate, liquid flow rate, NaOH concentration, and CO2 concentration. Experimental results demonstrated that the removal efficiency of CO2 increased with the rotational speed, liquid flow rate and NaOH concentration; however, decreased with the gas flow rate and CO2 concentration. The removal efficiency of CO2 was about 90% at a rotating speed of 1800 rpm, a gas flow rate of 9 L/min, a liquid flow rate of 0.5 L/min, an NaOH concentration of 1.0 mol/L, and a CO2 concentration of 1 vol%. Accordingly, the RPB with blade packings has great potential in the removal of CO2 from the exhaust gases.